Contracting under asymmetric information and externalities: an experimental study - Petra Nieken; Patrick W. Schmitz (Experimental Economics, 2023)
We investigate contract negotiations in the presence of externalities and asymmetric information in a controlled laboratory experiment. In our setup, it is commonly known that it is always ex post efficient for player A to implement a project that has a positive external effect on player B . However, player A has private information about whether or not it is in player A 's self-interest to implement the project even when no agreement with player B is reached. Theoretically, an ex post efficient agreement can always be reached if the externality is large, whereas this is not the case if the externality is small. We vary the size of the externality and the bargaining process. The experimental results are broadly in line with the theoretical predictions. However, even when the externality is large, the players fail to achieve ex post efficiency in a substantial fraction of the observations. This finding holds in ultimatum-game bargaining as well as in unstructured bargaining with free-form communication.
Keywords: D86; D82; D62; C78; C92; 330; Contracts; Externalities; Bargaining; Communication; Laboratory experiments